Soft methods for data science - Ferraro, Maria Brigida, 1982-; Giordani, Paolo; Vantaggi, Barbara; Gagolewski, Marek; Gil, María Á.; Grzegorzewski, Przemysłav; Hryniewicz, Olgierd (Springer, 2017)
This proceedings volume is a collection of peer reviewed papers presented at the 8th International Conference on Soft Methods in Probability and Statistics (SMPS 2016) held in Rome (Italy). The book is dedicated to Data science which aims at developing automated methods to analyze massive amounts of data and to extract knowledge from them. It shows how Data science employs various programming techniques and methods of data wrangling, data visualization, machine learning, probability and statistics. The soft methods proposed in this volume represent a collection of tools in these fields that can also be useful for data science.
Keywords: Big data -- Congresses.; Soft computing -- Congresses.; Electronic data processing -- Congresses.; elektronické knihy; electronic books